EFEK MODERASI PROFITABILITAS DAN LEVERAGE DALAM PENGARUH KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fakhri Ryan Cahyanto Putra; Budi Santoso; Ni Ketut Surasni (Master of Management, Mataram University, 2019)
This study aims to analyze the effect of dividend policy (DPR) on company value (PBV) with profitability (ROE) and leverage (DER) as moderation variable at manufacturing company listed in Indonesia Stock Exchange (IDX). Sampling technique is purposive sampling so the number of sample obtained are 16 companies, with year observation period are 2013-2016. Analysis technique used in this research is inferential statistic (regression linear) using Gretl, with 5 percent of level significant. It also performed descriptive statistic that include mean, median, minimum, maximum, and std. deviation. The results of this study indicate that dividend policy has a positive and significant effect on company value. Profitability is not able to moderate the influence of dividend policy on firm value and leverage can strengthen the influence of dividend policy on the value of companies in the manufacturing sector listed on the Indonesia Stock Exchange in 2013-2016.Keywords: Dividend Policy; Company Value; Profitability and Leverage